Gis analysis of patch use and group cohesiveness of bearded sakis (chiropotes sagulatus) in the upper essequibo conservation concession, guyana. Issue 2 (7th December 2012) - Shaffer, Christopher A.
Abstract This study examines how northern bearded sakis (Chiropotes sagulatus) in Guyana adjust group cohesiveness according to the distribution and quality of food patches. I introduce a GIS based method for quantifying food patch quality and how it relates to bearded saki group spread and group size. While the concept of food patch is central to most models of primate socioecology, defining what constitutes a patch has been notoriously problematic in primate studies. In addition, researchers have struggled to quantify group spread and group cohesiveness. Advances in spatial analysis software in the last decade now allow primate researchers to better quantify these variables. Group spread in bearded sakis was not significantly greater in lower quality patches and sakis were not more spread out during feeding than during other activities. However, the study group was significantly less spread out during social behavior. Bearded saki group size was significantly correlated with both monthly fruit abundance and patch quality. In fact, mean daily patch quality explained ∼40% of the variation in foraging party size. These results suggest that bearded sakis may rely on a highly fluid social structure to mitigate the effects of intragroup feeding competition while living in large groups. Sakis do not adjust group spread on a patch‐by‐patch basis but rather fission into smaller foraging parties when resources become scarce seasonally and patch quality is low. This study shows that GIS is a powerful tool for modeling the relationship between group cohesiveness and resource quality and distribution. Am J Phys Anthropol, 2013. © 2012 Wiley Periodicals, Inc.